Analisis Fenomenologi Tagar #AnalogSwitchOff terhadap Polarisasi Media Sosial Twitter pada Generasi Z - Della Fadhillah; Dianita Sari; Najla Zahrani Aulia; Dini Safitri (School of Communication Science and Media Business, 2023)
Twitter is a social media platform that allows its users to share messages using a special feature called hashtag. These features allow users to expand the reach of their tweets and attract more followers. This study aims to analyze the phenomenon of the hashtag #AnalogSwitchOff and its impact on polarization on Twitter. The research method used is a qualitative approach with phenomenological analysis techniques. The data used are tweets that use the #AnalogSwitchOff hashtag during a certain period, as well as data from in-depth interviews with eight active Twitter users. The results of the study show that the #AnalogSwitchOff hashtag triggers polarization among Twitter users, especially in terms of political and social differences. This hashtag is also used as a means of expressing opinions and criticism of government policies regarding broadcasting digitization. This study provides a deeper understanding of the use of hashtags in influencing public opinions and views on Twitter. Keywords: Twitter, social media, hashtag, polarization, #AnalogSwitchOf